ANALISIS KESALAHAN MULTIDIMENSIONAL SISWA DALAM PEMECAHAN MASALAH ALJABAR: TINJAUAN DARI PERSPEKTIF REPRESENTASI SEMIOTIK - Yana, Wa Ode Dahiana; Tamalene, Hanisa; Anastasyia, Neneng (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to uncover the multidimensional error patterns of students in solving algebra problems from the perspective of semiotic representation at various ability levels. This study used a qualitative approach involving 30 seventh-grade junior high school students. The research subjects were selected by purposive sampling, then six students were determined representing the high, medium, and low ability categories. Data were obtained through written tests and interviews, then analyzed based on Nolting's error classification, which includes misread direction error, careless error, concept error, application error, test procedure error, and transformation error. The results showed that students at all ability levels experienced difficulties in converting between representations (transformation error), especially from verbal to symbolic (algebraic expression) and symbolic to geometric expression. High-ability students were able to reason symbolically but failed to connect it to the visual context (graphical expression), while medium-ability students tended to use trial and error strategies that resulted in application errors. Students in the low-ability group showed concept errors and fundamental representation errors (transformation errors). In general, transformation errors were the most dominant type of error, followed by concept errors and application errors. These findings indicate that algebra learning needs to be designed by integrating various semiotic representations so that students' conceptual understanding can develop more deeply.